MNE responses to host country geopolitical conflict : The strategic MNE decisions of adjusting operations in Russia post-Ukraine invasion - Virta, Tytti (My University, 2024)
Geopolitical conflicts, such as war, influence the institutional environments in which MNEs operate. MNE responses to such geopolitical changes vary depending on different factors within the company, industry, or home country from not making any change to full-scale divestment. The still ongoing Russia-Ukraine conflict has garnered significant attention from Western countries and had major implications for MNEs operating in Russia. Formal and informal home and host country institutional pressures have forced MNEs to reconsider their strategies and possibly adjust their Russian operations according to those institutional demands. In this thesis, I examined the effect of geopolitical turbulence, war in particular, on the MNE host country’s business environment, the drivers influencing MNEs to make changes to their operations and the different MNE responses to these institutional pressures. I attempted to answer these questions on a general level and in the case of the 2022 Russian invasion of Ukraine through the lens of the institutional theory. I found that the significance of geopolitical events in a host country to an MNE can be major. Host country regulatory changes and uncertainty can cause disruptions to MNE operations. Home governments can for example impose sanctions on the MNE host country greatly impacting business activities to the point where divestment is considered, while host country governments can impose counter-sanctions hindering the possibility to exit. In addition to financial considerations, not complying with sanctions can cause damage to company reputation, forcing MNEs to calculate between operational costs of leaving and the reputational costs of staying. To respond to these varying institutional pressures, MNEs can in general employ 3 different tactics: conformity (complying with home pressures), avoidance (complying with host pressures) or balancing (finding a balance between both), depending on their specific situation and strategic goals. All of these three strategies have been used by Western MNEs in Russia since the 2022 invasion.
Keywords: geopolitics, conflict, war, divestment, Russia-Ukraine conflict, institutional theory